KEGIATAN PENGABDIAN KEPADA MASYARAKAT SOSIALISASI DAN EDUKASI PENGGUNAAN KOSMETIK BERBAHAYA PADA REMAJA DI SMA NEGERI 13 MEDAN - sulasmi, sulasmi (INSTITUT KESEHATAN DELI HUSADA, 2024)
Abstract Wellbeing could be a state of physical, mental, and social well-being, and not as it were free from malady but too living productively. The sort of wellbeing specialist may be a pharmaceutical specialist, namely a drug specialist. A drug specialist could be a proficient who has information and abilities within the field of drug store and has the specialist and obligation to carry out pharmaceutical errands. Beauty care products are materials utilized exterior the human body, such as skin, hair, nails, lips, outside genital organs, teeth, and mouth, particularly for cleaning, scenting, progressing appearance and body odor. Recently, numerous perilous components and chemicals in beauty care products; mercury, retinoic corrosive, hydroquinone, and rhodamine B. Side impacts from the utilize of perilous makeup can be facial skin harm, carcinogenicity, kidney disappointment, and teratogenicity. Utilize